The Role of Husband Involvement in Improving the Success of Exclusive Breastfeeding in Urban and Rural Areas: A Scoping Review - Maria Dulce Guterres; Mufdlilah Mufdlilah; Ismarwati Ismarwati (Indonesian Journal of Global Health Research, 2026)
Exclusive breastfeeding during the first six months of an infant’s life is an important strategy to improve maternal and child health. However, its success rates still vary between urban and rural areas. Husband involvement, as a form of family support, is one of the factors influencing the success of exclusive breastfeeding. This study aimed to map the scientific evidence regarding the role of husbands’ involvement in improving exclusive breastfeeding success in urban and rural settings through a scoping review approach. A literature search was conducted exclusively in the Scopus database for articles published between 2020 and 2025, following the PRISMA-ScR guideline. The search used predefined keywords including “father support,” “husband involvement,” “exclusive breastfeeding,” “urban,” and “rural,” combined with Boolean operators. A total of 108 articles were identified, of which 10 met the inclusion criteria and were further analyzed. The review findings revealed four main themes: (1) socio-cultural influences and family roles, (2) husbands’ practical and emotional involvement, (3) family knowledge, attitudes, and barriers to breastfeeding practices, and (4) education, counseling, and community support. Husbands’ support contributed to improved maternal breastfeeding self-efficacy, psychological stability, and sustainability of breastfeeding practices. Husband involvement plays an important role in supporting exclusive breastfeeding success. Higher husband involvement increases the likelihood of successful exclusive breastfeeding. Therefore, a family-based approach and a more inclusive healthcare system are needed to actively involve husbands in strategies to improve exclusive breastfeeding outcomes.